The Cultural Meaning of Traditional Expressions in Daily Speech of Using Community at Banyuwangi - Imam Suyitno (Humaniora, 2017)
This article aims to describe a variety of traditional expressions used by Using community at Banyuwangi in speaking. The variety of expressions is studied from the form, usage, and cultural meaning in communication. The data of traditional expression speech presented in the description sources from conversation of Using community in various speech situations. The result of the study shows that there are 6 categories of traditional expressions used in the Using speech community. The variety of the expressions used by the speaker to express a message, thoughts, feelings, or opinions to the speaking participan. Various things that can be conveyed through expression are praise, anger, aggravation, suggestions or advice, and pleasure. Using community utilizes the expressions to criticize, comment, ridicule, reassuring, stated, praising, reprimanding or blaming, complaining, remind, advise, and ask or beg. All of them are reflecting Using community culture in daily speech.